BeSAD … "it was truly an awful experience": an exploration of pre-service teachers' experiences and training needs to support pupils experiencing issues of bereavement, separation and divorce. (2nd January 2020) - Lynam, Aoife; McConnell, Barbara; McGuckin, Conor
ABSTRACT: Research exploring the well-being and pastoral care of pupils attending primary and post-primary schools has become an issue of increased discourse and growing national and international concern in recent years. Society often expects that teachers can support or facilitate pupils experiencing such issues; however, there is little research that explores whether pre-service teachers encounter these issues on school placement and how they approach such concerns if they do. This paper reports on a study of pre-service teachers (N = 354) from the Republic of Ireland (RoI) and Northern Ireland (NI) and the frequency with which they encountered issues relating to bereavement, separation and divorce (BeSAD). To address the training needs, six semi-structured interviews with experts in the area of BeSAD and Initial Teacher Education (ITE) are also included. The quantitative component of the research indicated that nearly half of the pre-service teachers had encountered pupils who had experienced some form of BeSAD whilst on school placement. Respondents lacked confidence when supporting pupils experiencing BeSAD, particularly in relation to separation and divorce. The interviews conducted with experts from NI and the RoI (N = 6) identified the core role that teachers play as advocates for pupils who have experienced BeSAD.